Community land regularisation approach review of six squatter upgrading projects in Greater Colombo - Thilakasiri, Ketawalage; Sheng, Yap Kioe; Weber, Karl E.; Wickramanayake, B.W.E.; Canadian International Development Agency/ Asian tnstitute of Technology - Canadian Universities Consortium/Partnership Project (CIDA/AIT - CUC/ PP) (Bangkok : Asian Institute of Technology, 1991)
This research explores the effectiveness 0f the community land regularisation approach which has been introduced under the Action Planning Strategy for granting security of tenure to urban poor in Sri Lanka. About 60 percent of the squatters settlements in the city of Colombo nave been reqularised within the last five years by this surveying approach. The researcher surveyed 10 completed and uncompleted housing clusters located in six upgrading projects which were regularised by three sub-approaches of the main approach. Households and officers surveys, field checking on physical changes and a review workshop on l and regularisation were conducted. Simple statistics, index numbers, correlation coefficient and Kendall's coefficient concordance were employed to analyse data. Although significant variations in the regularisation process and in the results according to the sub-approach were expected, the survey showed that variations due to the application of the three sub-approaches are very ir1significant. Results and processes vary due to settlement specific soc10-pnysica1 conditions. The results vary from cluster to cluster because each cl user traded-off results in order to maximise benefits in given prevailing socio-physical potentials and constraints. Officers supported communities by articulating community decisions to maximise qains throughout the process. Although delays in implementation took place , all the clusters were satiated with the results. So the approach is time-and-cost effective. The 1eve1 of community participation in dec1s1on-making and the satisfaction was high. This study showed that high awareness leads to strong community organisations, strong organisations lead to increased participation in decision-making, high participation leads to h1gn satisfaction. There is a strong correlation between the leve1 of participation in decision-making and the level of sat1stact1on. The correlation between participation and other aspects such as awareness and training are also strong, but correlation is not strong between participation and physical aspects, due to socio-physical constraints in the cluster. Since the approach has shown remarkable achievements, it has and hiqh potential for expanding in other context as well. Community participation in decision making should nevertheless be strengthened . comprehensive procedures and technical guidelines are proposal to guide the process.
A thesis submitted in partial fulfillment of the requirement for the award or the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Squatters -- Sri Lanka -- Colombo